A novel role for Friend of GATA1 (FOG-1) in regulating cholesterol transport in murine erythropoiesis. - Ioannis-Marios Roussis; David J Pearton; Umar Niazi; Grigorios Tsaknakis; Giorgio L Papadopoulos; Riley Cook; Mansoor Saqi; Jiannis Ragoussis; John Strouboulis (PLoS Genetics)
Friend of GATA1 (FOG-1) is an essential transcriptional co-factor of the master erythroid transcription factor GATA1. The knockout of the Zfpm1 gene, coding for FOG-1, results in early embryonic lethality due to anemia in mice, similar to the embryonic lethal phenotype of the Gata1 gene knockout. However, a detailed molecular analysis of the Zfpm1 knockout phenotype in erythropoiesis is presently incomplete. To this end, we used CRISPR/Cas9 to knockout Zfpm1 in mouse erythroleukemic (MEL) cells. Phenotypic characterization of DMSO-induced terminal erythroid differentiation showed that the Zfpm1 knockout MEL cells did not progress past the proerythroblast stage of differentiation. Expression profiling of the Zfpm1 knockout MEL cells by RNAseq showed a lack of up-regulation of erythroid-related gene expression profiles. Bioinformatic analysis highlighted cholesterol transport as a pathway affected in the Zfpm1 knockout cells. Moreover, we show that the cholesterol transporters Abca1 and Ldlr fail to be repressed during erythroid differentiation in Zfpm1 knockout cells, resulting in higher intracellular lipid levels and higher membrane fluidity. We also show that in FOG-1 knockout cells, the nuclear levels of SREBP2, a key transcriptional regulator of cholesterol biosynthesis and transport, are markedly increased. On the basis of these findings we propose that FOG-1 (and, potentially, GATA1) regulate cholesterol homeostasis during erythroid differentiation directly through the down regulation of cholesterol transport genes and indirectly, through the repression of the SREBP2 transcriptional activator of cholesterol homeostasis. Taken together, our work provides a molecular basis for understanding FOG-1 functions in erythropoiesis and reveals a novel role for FOG-1 in cholesterol transport.